A prospective cohort study assessing the appearance of retrieved aesthetic orthodontic archwires. (4th December 2017) - Collier, S.; Pandis, N.; Johal, A.; Qureshi, U.; Sharma, P. K.; Fleming, P. S.
Structured Abstract: Objectives: To investigate the appearance of three esthetic nickel titanium (NiTi) wires after 6 weeks of intra‐oral cycling and to determine the association between objective and subjective measures of esthetics. Setting and Sample Population: A prospective cohort study was undertaken involving participants undergoing upper fixed orthodontic appliance treatment with ceramic brackets. Materials and Methods: Fifty participants were assigned to one of three groups of NiTi esthetic wires (American Orthodontics Ever White™, Forestadent Biocosmetic™ and GAC High Aesthetic™), with wires retrieved after 6 weeks in situ. Participants completed a bespoke questionnaire exploring perceptions of wire esthetics. Objective measurement of coating loss was undertaken using a custom arch wire jig. Results: American Orthodontics Ever White™ had the greatest mean coating loss (50.7%) followed by Forestadent Biocosmetic™ (6%), with GAC High Aesthetic TM undergoing minimal loss (0.07%) ( P  < .001). The majority of coating loss with the American Orthodontics Ever White™ wires arose in the anterior region while Forestadent Biocosmetic™ wires and GAC High Aesthetic™ wires exhibited coating loss posteriorly ( P  < .001). These findings were reflected in the subjective assessment with a negative correlation found between coating loss and final Visual Analogue Scale scores ( P  < .001). Conclusions: Considerable esthetic variation between arch wires following 6 weeks of intraoral cycling was identified in this prospective cohort study. Intraoral cycling has a negative impact on participant perception of arch wire esthetics, and objective and subjective assessment of wire esthetics appears to be consistent.